Asset System Design Based on Accrual To Improvement Quality of Financial Information (A Case Study in the City of Pacitan) (International Journal of Management and Sustainability, 2015)
Accrual-based accounting is implemented in Goverment Accounting standards now (Government Regulation No. 71 of 2010). In Regulation 71 of 2010 depreciation shall be conducted on all goods belonging to the State/Region. Therefore, asset systems are adequate to accommodate the asset depreciation. In addition, asset system is necessary because asset management of the State/Regional is not optimal according to the Financial Oversight Bodies (BPK). This reasearch aims to create a prototype system of asset system in local government with a case study on the Government Pacitan. This reasearch is able to provide a solution to the problem of assets with an adequate information system.